Measurement of the total angiotensinogen and its reduced and oxidised forms in human plasma using targeted LC-MS/MS. - Dahabiyeh, Lina A; Tooth, David; Carrell, Robin W; Read, Randy J; Yan, Yahui; Pipkin, Fiona Broughton; Barrett, David A (Springer Nature, 2019)
Angiotensinogen (AGT) is a critical protein in the renin-angiotensin-aldosterone system and may have an important role in the pathogenesis of pre-eclampsia. The disulphide linkage between cysteines 18 and 138 has a key role in the redox switch of AGT which modulates the release of angiotensin I with consequential effects on blood pressure. In this paper, we report a quantitative targeted LC-MS/MS method for the reliable measurement of the total AGT and its reduced and oxidised forms in human plasma. AGT was selectively enriched from human plasma using two-dimensional chromatography employing concanavalin A lectin affinity and reversed phase steps and then deglycosylated using PNGase F. A differential alkylation approach was coupled with targeted LC-MS/MS method to identify the two AGT forms in the plasma chymotryptic digest. An additional AGT proteolytic marker peptide was identified and used to measure total AGT levels. The developed MS workflow enabled the reproducible detection of total AGT and its two distinct forms in human plasma with analytical precision of ≤ 15%. The LC-MS/MS assay for total AGT in plasma showed a linear response (R2 = 0.992) with a limit of quantification in the low nanomolar range. The method gave suitable validation characteristics for biomedical application to the quantification of the oxidation level and the total level of AGT in plasma samples collected from normal and pre-eclamptic patients.
Keywords: Angiotensinogen; Cys18; LC-MS/MS; Marker peptide; Pre-eclampsia; Redox switch; Angiotensinogen; Chemical Fractionation; Chromatography, Liquid; Chymotrypsin; Humans; Reproducibility of Results; Tandem Mass Spectrometry